2016
DOI: 10.1007/978-3-319-49655-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Twinkle Megane: Near-Eye LED Indicators on Glasses for Simple and Smart Navigation in Daily Life

Abstract: We present an eyeglass-type wearable device that has light emitting diode (LED) indicators on the frame of it. The device produces lighting patterns of 14 RGB LEDs near user's eyes as guiding information. Since installed LEDs on the frame of glasses are light and saving power, it is feasible to develop it for daily use. On the other hand, it cannot provide rich information such as text or images. In this study, we aim to realize a remote assistive system that provides assistive commands by lighting patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Firouzian et al [25] developed an eyeglass-type AR wearable device using RGB LEDs on the frame of the glasses to evaluate the possibility of using simple color cues as a means of remote navigation for elderly people with cognitive impairment. A study with 4 elderly participants with cognitive impairments showed that participants with mild impairments were able to follow the displayed instructions, participants with severe dementia failed to understand and follow them.…”
Section: Glassesmentioning
confidence: 99%
“…Firouzian et al [25] developed an eyeglass-type AR wearable device using RGB LEDs on the frame of the glasses to evaluate the possibility of using simple color cues as a means of remote navigation for elderly people with cognitive impairment. A study with 4 elderly participants with cognitive impairments showed that participants with mild impairments were able to follow the displayed instructions, participants with severe dementia failed to understand and follow them.…”
Section: Glassesmentioning
confidence: 99%
“…Given the repeated success in providing visual feedback through augmented glasses, we chose a similar approach for our design [12,27,32,33,35]. Instead of glasses, we decided to augment swimming goggles, the most ubiquitous swimming gear besides the swimsuit.…”
Section: Choosing a Feedback Modalitymentioning
confidence: 99%
“…The different navigation assistance for people with dementia identified in our systematic review are presented in the Supplementary material Table named Extracted Data which summarizes the data extracted from 23 published studies [8], [12], [13], [14], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36]. The table is divided into four sections respectively pertaining to (i) general information regarding the experiment, (ii) the advice provided by the device, (iii) the technology used and (iv) the experimental methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Also, visual light advice was found just as efficient as localized auditory advice and psychology students rated it as more practical and socially preferable to the auditory advice [13]. Second, Google Glass [26] and eyeglasses with RGB LEDs on the frame [18] as forms of augmented reality devices were used. Some minor difficulties were found to perceive the surrounding environment [26].…”
Section: Which Modalities Was the Navigation Advice Relying On?mentioning
confidence: 99%